The role of the miR-148/-152 family in physiology and disease - Friedrich, Michael; Pracht, Katharina; Mashreghi, Mir-Farzin; Jäck, Hans-Martin; Radbruch, Andreas; Seliger, Barbara (European Journal of Immunology, 2017)
MicroRNAs (miRNAs) are endogenously encoded 22 nt small non-coding RNAs. They function as key players of many cellular processes by base pairing with target mRNAs and thereby impairing gene expression at the post-transcriptional level. Recent findings demonstrate a critical role of many miRNAs in immune cell differentiation and immune responses, which is also associated with the development and progression of many tumor and non-tumor diseases. Here we review the multifaceted miRNA-148/-152 family members consisting of miR-148a, miR-148b and miR-152. Next to regulation mechanisms that control the expression of this miRNA family, we will focus on (i) the role of miR-148a in regulating B and T lymphocyte function and its role in associated diseases and (ii) the importance of miR-148/-152 family members for cancer initiation, tumor growth and metastasis formation. In addition, this review aims to highlight some selected targets of the miRNA-148/-152 family members, which are involved in the biology of cancer and maintenance of epigenetic patterns. In conclusion, members of the miR-148/-152 family might represent prognostic markers and/or potential therapeutic targets for treatment of autoimmune disorders, chronic inflammatory diseases and multiple types of cancer.
EVALuna2:13649